Inferring Causation from Cross-Sectional Data: Examination of the Causal Relationship between Hyperactivity–Impulsivity and Novelty Seeking - Wood, Alexis C.; Rijsdijk, Fruhling; Asherson, Philip; Kuntsi, Jonna (Frontiers in Genetics, 2011)
Previous research suggests an association between hyperactivity-impulsivity – one of the two behavioural dimensions that form attention deficit hyperactivity disorder – and the temperament characteristic of novelty seeking. We aimed to examine etiological links underlying the co-occurrence between these behaviours using a general population sample of 668 twin pairs, ages 7-10, for whom we obtained parent ratings in middle childhood; and pilot longitudinal data on 76 children. Structural equation modelling confirmed a shared genetic etiology (genetic correlation, rD=.81; 95% confidence intervals [CI]= .34-1.00) and showed that much (64%) of the covariation can be accounted for by shared genetic effects. In addition, causal paths were modelled between the two behaviours; 12% of the variance in novelty seeking at age 7 was accounted for by hyperactive-impulsive behaviors at the same age. The causal effects model fits with the current characterization of hyperactive-impulsive behaviors reflecting a heightened need for stimulation. This has important implications for the management of hyperactive-impulsive behaviors in clinical settings.